Experiências e reflexões sobre espaços urbanos de patrimônio e arte pública a partir da dimensão sociotécnica - SILVA, Carmen Lucia Souza da (Universidade Federal de Alagoas, 2023)
Besides presenting the Internet experience of the Urban Transcodification Project on virtualisation of historical monuments, which took place in Belém – PA, this paper aims to provide a theoretical reflection about how a socio-technical order has been effectively changing not only the interaction and production ways, but also how this order deals with the experience in effective urban spaces, which are pervaded by Public Art related heritage seen as spaces being affected by process of musealisation. The present paper also discusses the social use of heritage and the digital and virtual media, being as way to socialise information and knowledge or to consolidate a space that allows the access to the memory and experience of cultural heritage in cities. This theoretical-reflexive approach is based on researchers like Canclini (2006) who deals with historial monuments in Latin America, Levy (1999) and his issues on deterritorialisation, and Castells (2003) and FaustoNeto (2008) who argue about the socio-technical dimension.